Level of Understanding of the Professional Organization of Guidance and Counseling Among Guidance and Counseling Students in the Special Region of Yogyakarta - Farozin, Moh; Suwarjo, Suwarjo; Purnama, Diana Septi; Sari, Widya Juwita; Widyastuti, Dian Ari; Sulastriningsih, Sulastriningsih; Hasna, Salma Salsabila; Hidayah, Nor; Hazima, Haura (Buletin Konseling Inovatif, 2025)
The purpose of this study is to determine or assess the degree of understanding of the Guidance and Counselling professional organization in the Special Region of Yogyakarta, as well as the disparities in understanding among students based on level and gender. This study involved 238 guidance and counseling students from the special region of Yogyakarta, Indonesia who had completed the guidance and counseling profession course. A test instrument was developed to assess student’s understanding of (1) Articles of Association and Bylaws of the Indonesian Guidance and Counseling Association, (2) Organizational Attributes of the Indonesian Guidance and Counseling Association, and (3) and the Ethical Code of Guidance and Counseling, consisting of 79 multiple choice questions. Validity was assessed through expert judgment and analyzed using Aiken’s V. Reliability was tested through a reliability trial with Split Half Reliability analysis. Study's findings showed that students in the Special Region of Yogyakarta have a "high" level of understanding of the Articles of Association and Bylaws of the Indonesian Guidance and Counseling Association, Organizational Attributes of the Indonesian Guidance and Counseling Association, and the Ethical Code of Guidance and Counseling. Students in the Special Region of Yogyakarta comprehend the Code of Ethics of Guidance and Counselling at a "Very High" level. Meanwhile, when viewed from the differences in the level of understanding of students in the Special Region of Yogyakarta regarding learning outcomes about the Guidance and Counselling professional organization, which includes Articles of Association and Bylaws of the Indonesian Guidance and Counseling Association, Organizational Attributes of the Indonesian Guidance and Counseling Association, and the Ethical Code of Guidance and Counseling reviewed by gender, it shows that there is no significant difference in the average level of understanding between male and female students.